2014
DOI: 10.1007/s40124-014-0058-4
|View full text |Cite
|
Sign up to set email alerts
|

Striking While the Iron is Hot: Understanding the Biological and Neurodevelopmental Effects of Iron Deficiency to Optimize Intervention in Early Childhood

Abstract: Prenatal and early postnatal iron deficiency (ID) is associated with long-term neurobiological alterations and disruptions in cognitive, social, and behavioral development. Early life ID is particularly detrimental as this is a period of rapid neurodevelopment. Even after iron supplementation, cognitive and social disruptions often persist in formerly iron deficient individuals. Observational studies of the acute and long-term effects of early life ID yield different results based on the timing of ID. Further,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 62 publications
1
42
0
1
Order By: Relevance
“…Experimental evidence from animal studies suggests that fetal or neonatal ID impairs brain and especially hippocampal development [9] . Early ID has also been associated with defects in myelination and impairments in dopaminergic neurotransmission [10] . Effects of ID on development of these systems have been hypothesized to produce irreversible damage to cognitive performance.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Experimental evidence from animal studies suggests that fetal or neonatal ID impairs brain and especially hippocampal development [9] . Early ID has also been associated with defects in myelination and impairments in dopaminergic neurotransmission [10] . Effects of ID on development of these systems have been hypothesized to produce irreversible damage to cognitive performance.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Although the highest prevalence of iron deficiency in young and school-aged children is found in developing countries [2], it is also reported in industrialized areas [3]. In children, iron deficiency can have adverse effects on cognition, decrease motor activity, social attention and school performance, and increase susceptibility to infection [4].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous randomized trials performed on different pediatric age groups showed that iron supplementation prevented or corrected neurodevelopmental delay. These studies were mostly performed in low-or middle-income countries [55][56][57]. In the study from Costa Rica, iron deficiency and IDA were more frequent in infants fed with nonfortified-iron formula.…”
Section: Neurodevelopmental Signs and Symptomsmentioning
confidence: 99%